The Path of College Students’ Entrepreneurship Education Under Causal Attribution Theory From the Perspective of Entrepreneurial Psychology - Wang, Changlin; Liu, Qingquan; Li, Hongming; Liu, Yuanbing (Frontiers in Psychology, 2022)
The purpose of the study is to promote college students to actively respond to the national “Public Entrepreneurship and Mass Innovation” policies and calls, improve college students' entrepreneurial enthusiasm and their entrepreneurial ability, and cultivate their good entrepreneurial psychological states. First, the relevant content of entrepreneurship psychology and causal attribution theory is displayed. Second, the questionnaire of college students' entrepreneurship education is formulated and a questionnaire survey is conducted on University N based on the relevant content of entrepreneurship psychology. Subsequently, the management system of new venture A is taken as the research object to construct the management strategy of new ventures and simulate the implementation process. Finally, the questionnaire survey results of college students’ entrepreneurship education are analyzed and the corresponding entrepreneurship education path is formulated. Meanwhile, the implementation effect of the management strategy of new ventures is evaluated. After the questionnaire is sorted out, it is found that there are some problems in college students' entrepreneurship education, such as weak awareness of entrepreneurship, insufficient publicity, outdated curriculum, and unqualified teachers. The reasons for these problems are the constraints of traditional concepts, insufficient attention, and incomplete system construction. Therefore, a plan is made for overall entrepreneurship education, the publicity of the concept of entrepreneurship education is strengthened, and the setting of entrepreneurship education curriculum and the ability of the teachers for entrepreneurship education are improved. Through the evaluation of the simulation implementation of a new enterprise management strategy, it is found that the new management strategy can achieve the expected effect. Therefore, this study provides some references for the development of college students' entrepreneurship education and the management strategy of new ventures.